ENHANCING READING COMPREHENSION THROUGH THE CIRC METHOD IN ELEMENTARY EDUCATION - Refita Tiara Putri; Robiatul Munajah (El Midad, 2024)
Reading comprehension is a process of reading by students to recognize, understand, and at the same time retain the information contained in the reading content. Learning methods (Cooperative et al.) CIRC is a learning method that is specifically applied to learning to read and write in schools. This method encourages students to take an active role so that learning to read becomes more interesting, dynamic and enjoyable. The test data results obtained after carrying out each cycle have increased in cycle I by 70.20% and cycle II by 82.70%, which shows that in cycle II.  Using the CIRC learning method can improve reading comprehension skills in class IV. The average score for each cycle shows an increase in reading.